Fetal Neuroprotective Strategies: Therapeutic Agents and Their Underlying Synaptic Pathways - Elsayed, Nada A.; Boyer, Theresa M.; Burd, Irina (Frontiers in Synaptic Neuroscience, 2021)
Synaptic signaling is integral for proper brain function. During fetal development, exposure to inflammation or mild hypoxic-ischemic insult may lead to synaptic changes and neurological damage that impairs future brain function. Preterm neonates are most susceptible to these deleterious outcomes. Evaluating clinically used and novel fetal neuroprotective measures is essential for expanding treatment options to mitigate the short and long-term consequences of fetal brain injury. Magnesium sulfate is a clinical fetal neuroprotective agent utilized in cases of imminent preterm birth. By blocking N-methyl-D-aspartate receptors, magnesium sulfate reduces glutamatergic signaling, which alters calcium influx, leading to a decrease in excitotoxicity. Emerging evidence suggests that melatonin and N-acetyl-L-cysteine (NAC) may also serve as novel putative fetal neuroprotective candidates. Melatonin has important anti-inflammatory and antioxidant properties and is a known mediator of synaptic plasticity and neuronal generation. While NAC acts as an antioxidant and a precursor to glutathione, it also modulates the glutamate system. Glutamate excitotoxicity and dysregulation can induce perinatal preterm brain injury through damage to maturing oligodendrocytes and neurons. The improved drug efficacy and delivery of the dendrimer-bound NAC conjugate provides an opportunity for enhanced pharmacological intervention. Here, we review recent literature on the synaptic pathways underlying these therapeutic strategies, discuss the current gaps in knowledge, and propose future directions for the field of fetal neuroprotective agents.